Pengaruh Pop-Up Book Terhadap Hasil Belajar IPAS Kelas IV SDN Gugus III Kota Bengkulu - Hernelti, Yetri; Dalifa; Kurniawati, Ike (Universitas Bengkulu, 2025)
Finding out how pop-up book media affected fourth-grade students' scientific learning results at SD Negeri Gugus III in Bengkulu City was the aim of this study. This research is quantitative. To put it simply, the Matching The Pretest-Posttest Control Group Design approach is one kind of quasi-experimental study. Primary school students in Bengkulu City's third cluster made up the study's population. Fourth-grade state primary schools 57 and 48 in Bengkulu City served as the study's sample, and cluster random sampling was used as the selected sampling method. A cognitive aspect learning outcome exam consisting The learning aids consist of multiple-choice questions on both the pre-test and the post-test. the methodology applied to data analysis. Descriptive statistics, preliminary test analysis, and inferential analysis using the t-test are examples of quantitative data analysis techniques employed in this study. The findings of the inferential analysis show that t count (4.557) > t table (2.005). The two-sided significance criterion is 0.000 < 0.05. As a result, the average value of the science course of the experimental group (72) is different from the control group (57). The value varies because the experimental group and the control group were given different treatments. This shows how the use of pop-up book media in science learning for grade IV students of SD Negeri Gugus III Kota Bengkulu affects science learning outcomes.